PENGEMBANGAN E-LEARNING EDUKA PADA PEMBELAJARAN IPAS BERDIFERENSIASI KURIKULUM MERDEKA DI KELAS V SEKOLAH DASAR - Khoerunissa, Jihan; Sutisna, Atang (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
This research aims to develop an e-learning platform that is adapted to the Merdeka curriculum for Natural and Social Sciences (IPAS) subjects in class V at SDN Banjarwangi. The development method used is Research and Development (RD) following the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The analysis stage of this research involves collecting information about student needs and characteristics as well as the availability of facilities. Next, the E-Learning design is created based on the results of the analysis to ensure conformity with the Merdeka Curriculum and learning needs. The development stage involves creating interactive learning materials and modules according to the designs that have been created. Implementation was carried out by testing the E-Learning platform in class V at SDN Banjarwangi to evaluate its effectiveness and usefulness in supporting science and science learning. Evaluation is carried out by collecting feedback from teachers and students and analyzing student learning outcomes before and after using the E-Learning platform. It is hoped that the research results can contribute to the development of learning technology that meets the needs of the Merdeka curriculum and improve the quality of science and science learning in class V at SDN Banjarwangi through the use of an interactive and easily accessible E-Learning platform